KUALITAS PELAYANAN KESEHATAN DI RUANGAN RAWAT INAP BANGSAL PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH KABUPATEN SEKADAU - Teresia Ndam E.01108036 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The article raised the issue that the medical infrastructure and medical personnel in the room Inpatient Ward of Internal Medicine Hospital Sekadau inadequate. This article is intended to determine the constraints in the implementation of health care in patient room in the hospital wards Sekadau disease. This study was included in the descriptive research qualitative. To analyze more sharply, researchers used theory Ratminto. The results showed that the quality of care that the quality of health care in patient room in internal medicine wards not maximized due to several constraints such as, medical infrastructure has not been adequately, human resources in the room inpatient medicine wards inadequate, service process is slow, and General Hospital Sekadau still budget constraints. The conclusion of this research is in the room turns Inpatient Medicine Wards are still many shortcomings of medical facilities and medical personnel such as nurses and medical facilities for the procurement budget is still limited. Suggestions for this research is also expected to the hospital to be more selective in finding doctors and specialists to Sekadau District Government revisit the budget in order to finance general hospitals Sekadau. Keyword : Hospital, Quality of Service, Qualitative.